Silicon-carbon negative electrode material and preparation method thereof
A silicon-carbon negative electrode material with a core-shell structure and uniform dispersion addresses uneven dispersion and conductivity issues, achieving stable and efficient lithium-ion battery performance through even expansion and improved cycle life.
Patent Information
- Application Number
- CN202310725497.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
AI Technical Summary
Existing silicon-carbon composite materials for lithium-ion batteries face issues of uneven dispersion of silicon nanoparticles, poor conductivity, and large volume expansion, leading to decreased cycle performance and stability due to inconsistent expansion of graphite and silicon-carbon particles.
A silicon-carbon negative electrode material with a core-shell structure, where a high-capacity nano-silicon-carbon composite and graphite are uniformly dispersed, and a carbon coating layer is formed outside the core layer, with a specific mass ratio of silicon, graphite, and amorphous carbon, and a preparation method involving mechanical fusion and high-temperature treatment to achieve even expansion and improved conductivity.
The solution results in a material with uniform particle expansion, reduced cracking, and enhanced cycle stability, as evidenced by higher first coulombic efficiency and lower expansion rates, significantly improving the long-term performance of lithium-ion batteries.
Smart Images

Figure CN119170752A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a low-expansion, long-cycle silicon-carbon negative electrode material and a preparation method thereof, belonging to the technical field of lithium-ion batteries. Background Art
[0002] The advantages of lithium-ion batteries include large capacity, high voltage, high energy density, strong charge retention, no memory effect, long cycle life, green and pollution-free, low self-discharge, small size and light weight. They have gradually become the first choice for various portable electronic devices and high-capacity and high-power electric vehicles. With the demand for batteries with higher capacity and higher energy density, the theoretical specific capacity of graphite negative electrode materials is 372mAh·g -1 It is difficult to meet the demand, and high-capacity silicon negative electrode materials have become a research hotspot. Silicon is used as a negative electrode material for lithium-ion batteries. 15 The theoretical specific capacity of Si4 at room temperature is 3579 mAh g -1 , which is nearly 10 times that of graphite, making it a highly promising next-generation negative electrode material. However, during the charge and discharge process, silicon particles undergo a huge volume change (the change can reach 300% of the original volume), and silicon materials are prone to cracking and pulverization, resulting in the peeling of electrode active materials and conductive agents, and electrode active materials and current collectors, which seriously affects the battery's cycle performance. Therefore, solving the problem of volume expansion of silicon particles is the focus of research. Nano-sizing silicon materials and compounding them with carbon materials with good conductivity is currently the most studied solution.
[0003] Chinese invention patent CN102651476A discloses a lithium-ion battery silicon-carbon composite negative electrode material and a preparation method thereof. The silicon atoms are dispersed on the graphite nuclei by anion and cation charge adsorption method, so that the silicon atoms can be evenly coated on the graphite surface. Although the dispersion of silicon in the preparation process of the silicon-carbon composite material is effectively improved, and the initial efficiency and cycle stability of the silicon-carbon composite negative electrode material are improved, the graphite particle size is large and the specific surface area is low, while the nano-silicon particle size is small and the specific surface area is large. It is difficult for the graphite surface to provide a particularly large number of points for nano-silicon adsorption, which will inevitably lead to the aggregation of nano-silicon. During the charge and discharge process, the nano-silicon expands in volume due to the agglomeration effect. After multiple cycles, the nano-silicon will fall off the surface of the graphite particles, resulting in rapid decay of the material capacity.
[0004] Chinese invention CN113394386A discloses a silicon-carbon negative electrode material and its preparation method. The technical key points are that amorphous nano-silicon is first prepared, the amorphous nano-silicon is mixed with graphite nano-sheets, dispersants and solvents, and mechanical fusion is performed after drying. Finally, a silicon-carbon precursor is obtained at high temperature, and the silicon-carbon precursor is mixed with graphite to obtain a lithium-ion battery negative electrode material. This method can alleviate volume changes from its own structure by preparing amorphous silicon nano-materials with high purity and small grain size; then, it is mixed with a graphite material with a large specific surface area (>200m 2 / g) composite, because the specific surface area is comparable to that of silicon nanomaterials, the silicon nanomaterials can be evenly dispersed in the graphite material and in close contact by using a suitable process method, thereby avoiding a large number of silicon particles from agglomerating, and significantly improving the cycle performance of the composite material. However, in the later process of preparing the electrode sheet, the precursor material needs to be mixed with graphite, and the expansion degree of graphite and silicon-carbon precursor is inconsistent, which will lead to uneven expansion of the electrode sheet, causing separation of the active material graphite and the precursor material during long-term circulation, resulting in a decrease in long-term cycle performance.
[0005] Therefore, developing a low-expansion, long-cycle lithium-ion battery negative electrode material and a preparation method thereof is a technical difficulty in the field. Summary of the invention
[0006] The purpose of the present invention is to provide a silicon-carbon negative electrode material and a preparation method thereof, so as to solve the problems of uneven dispersion of existing silicon nanoparticles in silicon-carbon composite materials, poor conductivity, large expansion of silicon nanomaterials, etc. It is mentioned that high-capacity silicon-carbon negative electrode materials are mixed with graphite to form a certain capacity. In lithium battery applications, there are problems such as large volume expansion and inconsistent expansion of graphite and silicon-carbon particles, which lead to decreased cycle performance and stability.
[0007] The technical solution adopted by the present invention is:
[0008] A silicon-carbon negative electrode material, wherein the silicon-carbon negative electrode material has a core-shell structure, a high-capacity nano-silicon-carbon composite material and graphite are uniformly dispersed to form a core layer, and a carbon coating layer is formed outside the core layer;
[0009] The high-capacity nano-silicon-carbon composite material contains silicon, graphite and amorphous carbon, and the mass ratio of silicon, graphite and amorphous carbon is (40-60):(30-55):(2-15).
[0010] Preferably, the median particle size of the silicon-carbon negative electrode material is 5 to 20 μm; the median particle size of the high-capacity nano-silicon-carbon composite material is 1 to 50 μm; and the median particle size of the graphite is 1 to 50 μm.
[0011] Preferably, the graphite is one or a combination of two of artificial graphite, natural spherical graphite, natural flake graphite, and mesophase carbon microspheres.
[0012] The method for preparing the above silicon-carbon negative electrode material comprises the following steps:
[0013] S1: After the crystalline silicon block is processed by electrical discharge, a local high-temperature gasification treatment is performed at a temperature higher than the gasification temperature of silicon, and then ground and dried to obtain nano silicon powder;
[0014] S2: fully mixing nano silicon powder, graphite nanosheets, dispersant and solvent and drying to obtain a mixed powder of silicon and graphite; wherein the mass ratio of nano silicon powder, graphite nanosheets, dispersant and solvent is (1-3):(1-2):(0-1):(10-22);
[0015] S3: mechanically fusing the mixed powder and fully mixing it with an organic carbon source, stirring and coating it at high temperature, and then sintering and carbonizing it to obtain a high-capacity nano-silicon-carbon precursor; the mass ratio of the mixed powder to the organic carbon source is (1-20):1;
[0016] S4: Fully mix the high-capacity nano-silicon-carbon precursor, graphite, and organic carbon source, mechanically fuse them, and then sinter them at high temperature to obtain a silicon-carbon negative electrode material; wherein the mass ratio of the high-capacity nano-silicon-carbon precursor, graphite, and organic carbon source is 1:(5-12):(0.3-1.2).
[0017] Preferably, in step S2, the solvent is deionized water or an organic solvent.
[0018] Preferably, in step S2, the average particle size of the obtained nano silicon powder is 10-200 nm, the amorphization degree is 80-99%, and the average grain size is 1-20 nm. Preferably, in step S2, the drying temperature is 50-350°C.
[0019] Preferably, in steps S3 and S4, the organic carbon source is one or a combination of coal tar, coal pitch, petroleum asphalt, epoxy resin, phenolic resin, acrylic resin, furfural resin, polyvinyl chloride, polyacrylonitrile and polyvinylidene fluoride.
[0020] Preferably, in step S3, the high temperature coating conditions are: heating rate 1-20°C / min, temperature 100-1000°C, coating 0.5-30h;
[0021] The conditions for sintering and carbonization are: under protective gas conditions, heating rate 1-20°C / min, temperature 500-1250°C, sintering 1-20h;.
[0022] Preferably, in step S3, high-temperature stirring coating and sintering carbonization are all performed under gas protection, and the protective gas is nitrogen and / or an inert gas.
[0023] The beneficial effects of the present invention are:
[0024] 1. Use high-capacity nano silicon-carbon precursor, graphite and organic carbon source to re-granulate under the action of mechanical fusion, forming a carbon coating layer on the outer shell, and high-capacity nano silicon-carbon precursor and graphite are evenly dispersed inside, which can form a multi-layer expansion buffer effect and reduce the expansion rate of the particles; compared with the use of high-capacity silicon-carbon negative electrode material and graphite mixed into a certain capacity of negative electrode material, the particles have similar expansion degrees, and there will be no problem of inconsistent expansion of graphite and silicon-carbon particles leading to decreased cycle performance and stability;
[0025] 2. Use nano silicon powder with high amorphous degree and small grain size to make the silicon material isotropic, so that the silicon material can expand evenly in all directions when lithium ions are embedded, effectively alleviating the cracking of the silicon material;
[0026] 3. Use graphite nanosheets with high specific surface area to build a layered framework, and evenly disperse nano silicon powder between graphite nanosheets. There is a thin amorphous carbon layer between nano silicon and graphite, which increases the conductivity of the material. Because the specific surface areas of graphite nanosheets and nano silicon powder are similar, silicon particles can directly contact the graphite material, reducing the individual aggregation of silicon particles, making the dispersion of silicon particles more uniform, and the number of silicon particles between graphite nanosheets is small, causing less expansion. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the silicon-carbon negative electrode material obtained in Example 1;
[0028] Figure 2 The figure is a charge and discharge curve of a lithium-ion battery with a pole piece made of the battery silicon-carbon negative electrode material obtained in Example 1. DETAILED DESCRIPTION
[0029] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.
[0030] The present invention provides a method for preparing a silicon-carbon negative electrode material with low expansion and long cycle performance. The method comprises the following steps: a high-capacity nano-silicon-carbon precursor, graphite and an organic carbon source are re-granulated under the action of mechanical fusion to form a carbon coating layer as the outer shell and a high-capacity nano-silicon-carbon precursor and graphite uniformly dispersed inside to obtain a silicon-carbon negative electrode material with low expansion and long cycle performance.
[0031] Among them, the median particle size of the high-capacity nano-silicon carbon precursor is 1 to 50 μm, preferably 1 to 20 μm; the graphite is preferably one or a combination of two of artificial graphite, natural spherical graphite, natural flake graphite, and mesophase carbon microspheres, and the median particle size of the graphite is 1 to 50 μm, preferably 1 to 20 μm.
[0032] The organic carbon source is one or a combination of at least two of coal tar, coal pitch, petroleum pitch, epoxy resin, phenolic resin, acrylic resin, furfural resin, polyvinyl chloride, polyacrylonitrile and polyvinylidene fluoride, and an organic solvent can also be added to form a liquid carbon source for mechanical fusion; the median particle size of the carbon source material is 0.01 to 100 μm, preferably 0.1 to 20 μm;
[0033] The parameters of the mechanical fusion process are as follows: the gap between the tool and the cavity wall is 10 to 1000 mm, preferably 10 to 100 mm; the rotation speed is 500 to 1800 rpm, preferably 1200 to 1800 rpm; the fusion time is 0.2 to 10 h, more preferably 0.5 to 3 h.
[0034] The median particle size of the prepared silicon-carbon negative electrode material with low expansion and long cycle performance is 5 to 20 μm.
[0035] The high-capacity nano-silicon-carbon precursor is composed of nano-silicon particles, graphite nanosheets and an organic carbon source. The preparation method includes the following steps:
[0036] Step 1: The crystalline silicon bulk material is locally gasified at high temperature, and after cooling, micro-nano silicon particles formed by aggregation of silicon atom clusters are obtained;
[0037] Step 2: Mechanically grinding the micro-nano silicon particles obtained in step 1 to obtain silicon nanopowder;
[0038] Step 3: Mix the silicon nanopowder, graphite nanosheets, dispersant and solvent obtained in step 2, and dry them to obtain a first precursor;
[0039] Step 4: After mechanical fusion of the first precursor, the first precursor is mixed with an organic carbon source and stirred and coated at high temperature to obtain a second precursor;
[0040] Step 5: sinter and carbonize the second precursor at high temperature to obtain a high-capacity nano-silicon carbon precursor.
[0041] Wherein, in step 1, the silicon bulk material is subjected to local high-temperature treatment, the temperature needs to be higher than the gasification temperature of silicon, and then rapidly cooled, so that the sublimated atomic clusters are rapidly aggregated and cooled, and micro-nano silicon particles with small internal grains are obtained; the silicon bulk material is a single crystal silicon bulk or a polycrystalline silicon bulk; the local high-temperature gasification method is one of a laser ablation method and an electric discharge corrosion method (liquid phase, gas phase);
[0042] In step 2, the mechanical grinding method is one or a combination of wet grinding or dry grinding, preferably wet grinding; the wet grinding is one or a combination of two of a ball mill, a bead mill (vertical, horizontal), and a stirred mill; and the medium size of the wet grinding is 0.01 to 5 mm, preferably 0.01 to 0.5 mm; the medium material is one or a combination of at least two of zirconium oxide, aluminum oxide, silicon oxide, boron oxide, magnesium oxide, silicon carbide, tungsten carbide, silicon nitride, titanium nitride, cemented carbide, tool steel, etc.;
[0043] The solvent for wet grinding is deionized water or an organic solvent, preferably an organic solvent, wherein the organic solvent is one or a combination of at least two of alcohols, ketones, and amides; the alcohols are one or a combination of at least two of methanol, ethanol, ethylene glycol, polyethylene glycol, propanol, isopropanol, glycerol, n-butanol, and n-pentanol; and the ketones are one or a combination of at least two of acetone, methyl ethyl ketone, methyl propyl ketone, N-methyl pyrrolidone, methyl butyl ketone, and methyl amyl ketone.
[0044] Before mechanical grinding, the median particle size of the micro-nano silicon particles is 0.05-100 μm, preferably 0.1-50 μm, more preferably 0.1-10 μm, and further preferably 0.1-1.0 μm; after mechanical grinding, the average particle size of the obtained nano silicon powder is 10-200 nm, preferably 10-100 nm; the degree of amorphization is 80-99%, preferably 90-99%; the average grain size is 1-20 nm, preferably 1-15 nm.
[0045] In step 3, the thickness of the graphite nanosheet is 5 to 500 nm, preferably 5 to 100 nm; the specific surface area is 150 to 270 m 2 / g, preferably 200 to 270 m 2 / g. The graphite nanosheets are preferably one or a combination of two of artificial graphite, natural spherical graphite, natural flake graphite, and mesophase carbon microspheres;
[0046] The dispersant is one or more combinations of sodium hexametaphosphate, sodium dodecyl sulfate, triethylhexyl phosphate, hexaalkyltrimethylammonium bromide, polyetherimide, and polyacrylamide; the solvent is deionized water or an organic solvent, preferably an organic solvent, the organic solvent is one or a combination of at least two of alcohols, ketones, and amides, the alcohol is one or a combination of at least two of methanol, ethanol, ethylene glycol, polyethylene glycol, propanol, isopropanol, glycerol, n-butanol, and n-pentanol; the ketone is one or a combination of at least two of acetone, methyl ethyl ketone, methyl propyl ketone, N-methyl pyrrolidone, methyl butyl ketone, and methyl amyl ketone.
[0047] The mixing method is one of high-speed stirring and ultrasound or a combination of the two, and the time is 1 to 10 hours; the drying method adopts a spray dryer, a vacuum distillation machine or a freeze dryer for drying; when a spray dryer is selected for drying, the inlet temperature of the spray dryer is 90 to 350° C., preferably 120 to 180° C.; the outlet temperature is 50 to 250° C., preferably 75 to 150° C.
[0048] In step 4, the mechanical fusion parameters are: the gap from the tool to the cavity wall is 10 to 1000 mm, preferably 10 to 100 mm; the rotation speed is 500 to 1800 rpm, preferably 1200 to 1800 rpm; the fusion time is 0.2 to 10 h, preferably 0.5 to 3 h; the mixing is performed by mixing the first precursor and the organic carbon source through VC mixing, the mixing speed is 500 to 1500 rpm, preferably 1000 to 1500 rpm; the mixing time is 0.5 to 10 h, preferably 3 to 5 h.
[0049] The organic carbon source is one or a combination of at least two of coal tar, coal pitch, petroleum asphalt, epoxy resin, phenolic resin, acrylic resin, furfural resin, polyvinyl chloride, polyacrylonitrile and polyvinylidene fluoride; and the median particle size of the organic carbon source is 0.01 to 100 μm, preferably 0.1 to 20 μm; the ratio of the first precursor to the organic carbon source is (1-20):1, preferably (3-5):1.
[0050] During the high-temperature stirring coating process, the spindle speed is 100-1000 rpm, preferably 150-500 rpm; the coating temperature is 100-1100°C, preferably 300-850°C; the heating rate is 1-20°C / min, preferably 3-10°C / min; the coating time is 0.5-30h, preferably 8-20h;
[0051] In step 5, the high-temperature sintering carbonization temperature is 500-1250°C, preferably 800-1200°C; the heating rate is 1-20°C / min, preferably 5-15°C / min; and the sintering time is 1-20h, preferably 5-15h.
[0052] In step 4 and step 5, high-temperature stirring coating and high-temperature sintering carbonization are both carried out under the protection of a protective gas, and the protective gas is one or a combination of at least two of nitrogen, argon, helium, neon, krypton and xenon.
[0053] Example 1
[0054] Preparation process of nano silicon powder
[0055] The crystalline silicon bulk material is processed by electric spark discharge machining, with a discharge pulse width of 120μs, a duty cycle of 1:5, an open circuit voltage of 180V, local high-temperature gasification, and deionized water as the working fluid. After cooling, micro-nano silicon particles formed by clusters of silicon atoms are obtained; then mechanical grinding is carried out, using zirconia grinding balls with a diameter of 0.1mm, an edge linear speed of 14.5m / s, ethanol as the grinding solvent (with 1wt% sodium hexametaphosphate added as a dispersant), and a ball milling time of 5h to obtain nano silicon particles with an average particle size of 100nm, which are then spray dried to obtain nano silicon powder.
[0056] Preparation process of high capacity nano-silicon carbon precursor
[0057] Step 1: weigh 1 kg of nano-silicon powder, 1 kg of graphite nanosheets, and 18 kg of ethanol (in a ratio of 1:1:18), disperse them in a ball mill for 6 hours, disperse the agglomerated silicon particles, and fully mix them with the graphite nanosheets;
[0058] Step 2: spray-dry the mixed slurry under the protection of high-purity nitrogen (purity 99.999%) to obtain dry silicon and graphite mixed powder;
[0059] Step 3: After the dried mixed powder is mechanically fused for 1 hour (the gap between the tool and the cavity wall is 50mm; the rotation speed is 1500rpm), 1.8kg of the mixed powder and 0.384kg of asphalt are weighed and put into the high-temperature coating equipment. Under the protection of high-purity nitrogen, the materials are first stirred at 500rpm for 3 hours to fully mix, and then heated to 150℃ at 120rpm and a heating rate of 5℃ / min for 5 hours, then heated to 500℃ at the same heating rate, kept warm for 2 hours, and finally heated to 900℃ for 3 hours, and naturally cooled to room temperature. The residual carbon rate of asphalt after carbonization at 900℃ is 52%. After high-temperature carbonization, the ratio of silicon: graphite: amorphous carbon is 45:45:10, and a high-capacity nano-silicon-carbon precursor is obtained.
[0060] Preparation process of low expansion and long cycle nano silicon carbon
[0061] Weigh 1kg of high-capacity nano-silicon-carbon precursor that has passed through a 325-mesh sieve, 8.75kg of commercial artificial graphite, and 0.5kg of asphalt, mix them at a high speed of 1000rpm in a VC mixer for 1h, then transfer the materials to a mechanical fusion machine at a speed of 1000rpm for 1h, then transfer the materials to a box furnace and heat them to 1000℃ at a heating rate of 5℃ / min, keep them warm for 2 hours, and then cool them naturally to obtain a low-expansion, long-cycle nano-silicon-carbon negative electrode material, the SEM image of which is shown in the figure. Figure 1 shown.
[0062] Comparative Example 1
[0063] The difference from Example 1 is that in the preparation process of low-expansion, long-cycle nano-silicon carbon, this comparative example directly mixes the high-capacity nano-silicon carbon precursor with graphite to form a silicon-carbon negative electrode material of a certain capacity without going through a mechanical fusion process.
[0064] Specifically, 1 kg of high-capacity nano-silicon-carbon precursor was weighed, directly mixed with 9 kg of commercial artificial graphite by VC, and mixed at a speed of 1000 rpm for 1 hour to obtain a silicon-carbon negative electrode material.
[0065] Comparative Example 2
[0066] The difference from Example 1 is that nano silicon powder (SiNPs) is directly used as the raw material for preparing the high-capacity nano silicon-carbon precursor, rather than being obtained by electric spark discharge machining and ball milling.
[0067] The nano-silicon powder is mixed and ball-milled with graphite nanosheets, and then mechanically fused and carbon-coated using the same method to obtain a silicon-carbon precursor, which is then mixed, fused and subjected to high-temperature treatment with a carbon source and graphite to prepare a silicon-carbon composite material.
[0068] Comparative Example 3
[0069] The difference from Example 1 is that in the preparation process of the high-capacity nano-silicon carbon precursor, the mixed powder is not subjected to mechanical fusion treatment in step 3.
[0070] Electrochemical performance test
[0071] The silicon-carbon negative electrode materials prepared in Example 1 and Comparative Examples 1-3 were subjected to pole piece preparation, button cell assembly and electrochemical performance testing. The specific steps are as follows: the silicon-carbon negative electrode materials prepared in Example 1 and Comparative Examples 1-3 were mixed with conductive carbon black, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass ratio of 95.4:1:1.3:2.5, wherein CMC was a solution with a mass fraction of 2%. The slurry was dispersed at 10000rpm with a high-speed shear mixer (Fluko FA25, Germany) for 30 minutes. The stirred slurry was then evenly coated on a copper foil of 8μm thickness. After natural drying, the copper foil was placed in a vacuum drying oven at 80°C and dried for 10 hours. After rolling, the pole piece was punched and cut into discs with a diameter of 13mm. 2032 button cells were assembled in a glove box protected by high-purity argon. Metal lithium foil was used for the electrode, and a polypropylene porous membrane (Celgard 2400) was used as the diaphragm. 1M LiPF6 and 5wt% fluoroethylene carbonate were added to a mixed solution of ethylene carbonate / dimethyl carbonate / ethyl methyl carbonate in a volume ratio of 1:1:1 as electrolyte. Battery charge and discharge tests were performed in a blue-electric test system. The test voltage range of the silicon-carbon negative electrode material was 0.005V-2.0V (vs. Li+ / Li). The test results are shown in Table 1. The charge and discharge curve of the lithium-ion battery made of the electrode made of the silicon-carbon negative electrode material obtained in Example 1 is shown in Table 1. Figure 2 The test procedure is to cycle 3 times with a small current density of 0.05C, charge and discharge cycles at a rate of 0.1C, the voltage range is 0.005V-2.0V, the number of cycles is 100 times, and the expansion rate test is to disassemble the fully charged button battery to measure the expansion rate of the electrode.
[0072] Table 1
[0073]
[0074] It can be seen from the data in Table 1 that the nano silicon-carbon negative electrode material prepared by Example 1 has a higher first coulombic efficiency, a lower first lithium insertion full charge expansion rate and a good cycle retention rate, while the first efficiency and cycle retention rate of comparative examples 1-3 are lower, and the first lithium insertion full charge expansion rate is higher, which further proves that the fusion of the high-capacity nano silicon precursor with graphite and an organic carbon source can form a multi-layer expansion buffer, and the particles have a similar expansion degree, and there will be no problem of inconsistent expansion of graphite and silicon-carbon particles leading to decreased cycle performance and stability, which greatly improves the cycle stability of the material.
[0075] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material has a core-shell structure, the high-capacity nano-silicon-carbon composite material and graphite are evenly dispersed to form a core layer, and a carbon coating layer is formed outside the core layer; The high-capacity nano-silicon-carbon composite material contains silicon, graphite and amorphous carbon, and the mass ratio of silicon, graphite and amorphous carbon is (40-60):(30-55):(2-15).
2. The silicon-carbon negative electrode material according to claim 1, characterized in that: The median particle size of the silicon-carbon negative electrode material is 5 to 20 μm; the median particle size of the high-capacity nano silicon-carbon composite material is 1 to 50 μm; and the median particle size of the graphite is 1 to 50 μm.
3. The silicon-carbon negative electrode material according to claim 1, characterized in that: The graphite is one or a combination of two of artificial graphite, natural spherical graphite, natural flake graphite and mesophase carbon microspheres.
4. The method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1: After the crystalline silicon block is processed by electrical discharge, a local high-temperature gasification treatment is performed at a temperature higher than the gasification temperature of silicon, and then ground and dried to obtain nano silicon powder; S2: fully mixing nano silicon powder, graphite nanosheets, dispersant and solvent and drying to obtain a mixed powder of silicon and graphite; wherein the mass ratio of nano silicon powder, graphite nanosheets, dispersant and solvent is (1-3):(1-2):(0-1):(10-22); S3: mechanically fusing the mixed powder and fully mixing it with an organic carbon source, stirring and coating it at high temperature, and then sintering and carbonizing it to obtain a high-capacity nano-silicon-carbon precursor; the mass ratio of the mixed powder to the organic carbon source is (1-20):1; S4: Fully mix the high-capacity nano-silicon-carbon precursor, graphite, and organic carbon source, mechanically fuse them, and then sinter them at high temperature to obtain a silicon-carbon negative electrode material; wherein the mass ratio of the high-capacity nano-silicon-carbon precursor, graphite, and organic carbon source is 1:(5-12):(0.3-1.2).
5. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step S2, the solvent is deionized water or an organic solvent.
6. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step S2, the average particle size of the obtained nano silicon powder is 10-200 nm; the degree of amorphization is 80-99%; and the average grain size is 1-20 nm.
7. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step S2, the drying temperature is 50-350°C.
8. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In steps S3 and S4, the organic carbon source is one or a combination of coal tar, coal pitch, petroleum pitch, epoxy resin, phenolic resin, acrylic resin, furfural resin, polyvinyl chloride, polyacrylonitrile and polyvinylidene fluoride.
9. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step S3, the high temperature coating conditions are: heating rate 1-20°C / min, temperature 100-1000°C, coating 0.5-30h; The conditions for sintering and carbonization are: under protective gas conditions, heating rate 1-20°C / min, temperature 500-1250°C, sintering 1-20h;.
10. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In step S3, high-temperature stirring coating and sintering carbonization are all performed under gas protection, and the protective gas is nitrogen and / or inert gas.
Citation Information
Cited By
Silicon-carbon composite material as well as preparation method and application thereof
CN120300160A
Preparation method of silicon-carbon negative electrode material of lithium ion battery and silicon-carbon negative electrode material
CN121565835A
Silicon-carbon composite negative electrode material with high silicon content and stable interface as well as preparation method and application of silicon-carbon composite negative electrode material
CN122202289A
